Chronic idiopathic urticaria and autoimmunity: frequency and association in patients with positive versus negative autologous serum skin test - Jindal, Rashmi; Roy, Samarjit; Nagrani, Prateek (International Journal of Research in Medical Sciences, 2017)
Background: Chronic idiopathic urticaria is a subset of urticaria where no known trigger is identifiable. Almost half of these patients have an autoimmune basis of their disease. Autologous serum skin test (ASST) is an easy to perform test to identify this subgroup. However, frequency and association of positive ASST with other markers of autoimmunity remains to be studied. The present study was aimed to find out the same. Methods: Chronic idiopathic urticaria patients were divided into two groups on the basis of ASST. These were further compared for their clinical characteristics including age, gender, duration of disease and urticaria activity score. Also investigation profile including serum IgE levels, anti TPO antibodies, antiTSH and antinuclear antibodies were compared. Results: There were no statistical differences in the age, gender, duration of disease and urticaria activity score in the ASST positive and negative patients. Serum IgE levels though lower in ASST positive group were not statistically different. Frequencies of AntiTPo antibodies, antiTSH and antinuclear antibodies were also comparable in the two groups. Conclusions: ASST positive and negative groups can’t be distinguished clinically. Also autoimmunity was found to be associated with both ASST positive and negative groups.